Dampak Price, Green Knowledge, dan Electronic Word of Mouth terhadap Purchase Intention Pada Sepeda Listrik di Kediri - Fransiska, Chiva; Ayuanti, Rafikhein Novia; Saputra, Beny Mahyudi (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the effect of price, green knowledge, and electronic word of mouth (eWOM) on purchase intention toward electric bicycles in Kediri City. A quantitative approach with a causal-comparative design was employed. Data were collected through an online questionnaire involving 112 respondents familiar with electric vehicle concepts, using purposive sampling. The validity and reliability tests confirmed that all research instruments were valid and reliable. Data analysis was performed using multiple linear regression with SPSS version 26. The results reveal that all independent variables have a positive and significant effect on purchase intention, with an R² value of 0.893. Among them, eWOM has the most dominant influence compared to price and green knowledge. These findings indicate that reasonable price perception, adequate environmental knowledge, and positive online reviews simultaneously enhance consumers’ purchase intention for electric bicycles. This study supports the Theory of Planned Behavior in explaining eco-friendly purchasing behavior and provides strategic implications for companies to apply value-based pricing, environmental education campaigns, and effective digital promotion strategies.